Tropical bubbles : asset prices in Latin America, 1980-2001 - Herrera Aguilera, Santiago 1989- (Policy research working paper, 2001)
The authors examine if observed asset prices in Latin America depart significantly from fundamentals-determined levels. These departures, or bubbles, are found to be equally determined by both country-specific and common external variables, contrary to previous studies that found that local factors were predominant in asset price determination in Latin America